Evolving Legal Responsibilities and Challenges in Prosecuting Cybercrime Across Jurisdictions: Tanggung Jawab Hukum yang Berkembang dan Tantangan dalam Menindak Kejahatan Dunia Maya di Seluruh Yurisdiksi - Taqi, Riyadh Hussain (Academia Open, 2025)
General Background: In the digital age, cybercrime has emerged as a sophisticated and transnational threat, endangering global security, economic stability, and individual privacy. Specific Background: The rapid evolution of cyber-offenses challenges traditional legal frameworks, particularly in defining liability and proving criminal intent in virtual environments. Knowledge Gap: Despite ongoing reforms, there is limited clarity on how legal systems conceptualize and apply core criminal law principles such as actus reus and mens rea to cybercrime, particularly across diverse jurisdictions. Aims: This study investigates the evolving definitions of criminal responsibility in cybercrime, analyzes the adaptation of legal systems to digital threats, and explores the evidentiary challenges in proving guilt within cyberspace. Results: The findings confirm that while actus reus and mens rea remain applicable, their interpretation in digital contexts becomes significantly complex. Key challenges include jurisdictional disputes, offender anonymity, and digital evidence admissibility. Novelty: Through doctrinal and comparative legal research, this study presents a multi-jurisdictional analysis spanning the U.S., E.U., Asia, and the Middle East, offering a comprehensive perspective on legal convergence in addressing cybercrime. Implications: Legal systems must innovate by enacting precise cybercrime statutes, investing in digital forensic capabilities, enhancing professional education, and fostering global legal harmonization to ensure effective cyber justice. Highlights: Redefining Crime Elements: Adapting actus reus and mens rea digitally. Legal Reform Needed: Update laws, boost digital investigation capacity. Global Coordination Required: Harmonize international laws for cybercrime enforcement. Keywords: Cybercrime, Criminal Responsibility, Digital Evidence, Comparative Law, Legal Reform